2018
DOI: 10.1007/s00345-018-2428-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiparametric and biparametric MRI of the prostate: are gadolinium-based contrast agents needed for routine examinations?

Abstract: Omitting DCE did not lead to significant differences in diagnostic accuracy or tumor detection rates when using the PI-RADS 2 scoring system. According to these data, it seems reasonable to use a biparametric approach for initial routine prostate MRI. This could decrease examination time and reduce costs without significantly lowering the diagnostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 32 publications
7
73
0
1
Order By: Relevance
“…The addition of DWI and DCE led to a reduction in LIKERT 3 lesions from 44.6% to 33.5% and a corresponding increase in LIKERT 5 lesions from 12.0% to 37.9%. This shift has also been observed in similar studies using PI-RADSv2 where DCE had a role in distinguishing equivocal lesions in the peripheral zone [28]. It has been suggested that the higher proportion of equivocal lesions could be addressed by only performing the additional sequences in those cases where such a lesion is identified; however, this would require scans to be immediately reported or the patient to return for a second scan at a later date.…”
Section: Discussionsupporting
confidence: 59%
“…The addition of DWI and DCE led to a reduction in LIKERT 3 lesions from 44.6% to 33.5% and a corresponding increase in LIKERT 5 lesions from 12.0% to 37.9%. This shift has also been observed in similar studies using PI-RADSv2 where DCE had a role in distinguishing equivocal lesions in the peripheral zone [28]. It has been suggested that the higher proportion of equivocal lesions could be addressed by only performing the additional sequences in those cases where such a lesion is identified; however, this would require scans to be immediately reported or the patient to return for a second scan at a later date.…”
Section: Discussionsupporting
confidence: 59%
“…An initial 3502 studies underwent title and abstract screening, of which 127 studies were retrieved for full‐text review. In all, 31 studies reporting on 9480 patients (4296 with prostate cancer) met the inclusion criteria for meta‐analysis; 25 studies reported on mpMRI DTA (7000 patients, 2954 with prostate cancer), 12 studies reported on bpMRI DTA (2716 patients, 1477 with prostate cancer), and six studies directly compared mpMRI and bpMRI (2047 patients, 1063 with prostate cancer). Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63].…”
Section: Resultsmentioning
confidence: 99%
“…Table provides a summary of the included studies [22,34––63], while Table provides a risk of bias summary of the included studies [22,34––63]. Seven studies were at high risk of bias , four were at low risk of bias , and the remaining 18 studies had an unclear risk of bias due to at least one of the four domains .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether DCE should be included in the multiparametric standard has always been a controversial issue [28], showing both supporters and opposers. Pros and cons of DCE are summarised in Table 3 [13,28,[30][31][32][33].…”
Section: Non-contrast Biparametric Mrimentioning
confidence: 99%